Pelatihan dan Pendampingan Pembuatan Kemasan Onde–onde Ketawa untuk Meningkatkan Daya Jual Produk pada UMKM Mugi Berkah - Syakhroni, Akhmad; Khoiriyah, Nuzulia; Marlyana, Novi; M Maknun; Mas'ud, Ahmad Afifudin (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
Competition in the world of Micro, Small, and Medium Enterprises (MSMEs) is currently very tight, requiring business players to constantly innovate to survive, not only in terms of product quality but also in packaging. Product packaging in MSME competition is a significant challenge that must be faced by MSMEs in marketing their products. UMKM Mugi Berkah is a home industry that produces snacks called